2004
DOI: 10.1021/jo035204n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Alkylated Aminofluorenes by Palladium-Catalyzed Substitution at Halofluorenes

Abstract: New N-substituted 2-amino-9,9-dialkylfluorenes optionally bearing electron-withdrawing substituents such as nitro or cyano in position 7 can be synthesized starting from 2-halo-9,9-dialkylfluorenes by Pd-catalyzed substitution with amines. Chiral amino groups can be introduced by this method too. 2-N,N-Dimethylamino-7-nitro-9H-fluorene was obtained in a convenient way by reductive amination. The N-substituted 2-amino-7-nitro-9H-fluorenes are promising candidates for fluorescence probes for femtosecond solvatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
(17 reference statements)
2
24
0
Order By: Relevance
“…de-ANF was purchased from Sigma-Aldrich (98%) and purified by chromatography on silica to yield the analytically pure material, and dm-ANF molecules were synthesized as described in literature. 35 Purification of dm-ANF was difficult, but achieved by repeated chromatography on silica, to yield the analytically pure material. NMR spectra of the pure compounds are presented in the ESI † ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…de-ANF was purchased from Sigma-Aldrich (98%) and purified by chromatography on silica to yield the analytically pure material, and dm-ANF molecules were synthesized as described in literature. 35 Purification of dm-ANF was difficult, but achieved by repeated chromatography on silica, to yield the analytically pure material. NMR spectra of the pure compounds are presented in the ESI † ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[12] However, no trinuclear complex has been observed for CPP synthesis.Polyfluorenes,w hich contain rigid biphenyl unit, have emerged as an attractive class of conjugatedp olymers for applications to organic electronics due to excellent fluorescent and electroluminescence ability and high charge-carrier mobility of fluorene unit. [13] Therefore, synthesis of cyclic oligomers of fluorenederivativesw ould be of great interest.During the platinum-mediated synthesiso ft he cyclic fluorene derivatives, we found that the assembly of 2,7-bis(trimethylstannyl)-9,9-dimethyl-2,7-fluorene (1) [14] with [PtCl 2 (cod)] (cod = 1,5-cyclooctadiene) mainly afforded at riangle-shaped complex with ap latinum at each vertex. Reductivee limination of platinum from the trianglec omplex gave [3]cyclo-9,9-dimethyl-2,7-fluorene( [3]CFR).…”
mentioning
confidence: 99%
“…with an 80% yield [76]. The nitro groups of both 30 and 31 were efficiently reduced to amino functionality per our recent report on commercially available Fe 3 O 4 nanoparticles as a heterogeneous catalyst for nitro group reduction in combination with hydrazine monohydrate [77].…”
Section: Chemistrymentioning
confidence: 87%